Generative AI in clinical (2020–2025): a mini-review of applications, emerging trends, and clinical challenges - Fahad, Nafiz; Rabbi, Riadul Islam; Benta Hasan, Sumayea; Sultana Prity, Fariya; Ahmed, Rasel; Ahmed, Farhana; Hossen, Md. Jakir; Liew, Tze Hui; Sayeed, Md Shohel; Ong Michael Goh, Kah (Frontiers in Digital Health, 2025)
Generative artificial intelligence (G-AI) has moved from proof-of-concept demonstrations to practical tools that augment radiology, dermatology, genetics, drug discovery, and electronic-health-record analysis. This mini-review synthesizes fifteen studies published between 2020 and 2025 that collectively illustrate three dominant trends: data augmentation for imbalanced or privacy-restricted datasets, automation of expert-intensive tasks such as radiology reporting, and generation of new biomedical knowledge ranging from molecular scaffolds to fairness insights. Image-centric work still dominates, with GANs, diffusion models, and Vision-Language Models expanding limited datasets and accelerating diagnosis. Yet narrative (EHR) and molecular design domains are rapidly catching up. Despite demonstrated accuracy gains, recurring challenges persist: synthetic samples may overlook rare pathologies, large multimodal systems can hallucinate clinical facts, and demographic biases can be amplified. Robust validation, interpretability techniques, and governance frameworks therefore, remain essential before G-AI can be safely embedded in routine care.